Evaluation of liver function test abnormalities in patients having COVID-19 according to severity of disease - Waheed, Ayesha; Nawaz, Rizwana; Riaz, Marryam; Ahmad, Bilal; Faisal, Shahrukh; Zafar, Shamail (International Journal of Research in Medical Sciences, 2022)
Background: COVID-19 infection affects all major organs of body in addition to lungs. Damage done to liver varies from being hepatocellular, obstructive or mix pattern. The aim of the study was to evaluate abnormalities of LFTs, in COVID-19 patients according to disease severity in our population. Methods: A cross sectional study, conducted at GTTH and Surgimed Hospital Lahore, on 100 patients who presented with COVID-19 in between October 2020 and September 2021. According to Symptoms, patients were marked as having mild, moderate or severe disease. Bilirubin, Albumin, ALP, ALT, AST, GGT, LDH and prothrombin time were checked at admission and subsequently. Data was analyzed using SPSS v23. Laboratory values were computed in each severity category and SD values, odds ratio, 95% confidence intervals were studied in logistic regression models. P value<0.05 were considered statistically significant. Results: Among studied patients, 66% were male, 34% were female, mean age of 44.68±9.36 and range of 29-68 years. 29% were with mild disease, 40% with moderate disease, and 21% with severe disease level. 80% cases with rural background had moderate/severe disease levels while only 14.3% cases with severe levels were from urban areas. Only direct bilirubin showed a statistical significance with p value<0.05 in all severity groups. Other LFT’s didn’t show any significance between different severity groups. Conclusions: Among Liver function markers only bilirubin was related to COVID-19 disease and proportional to severity of disease.